2008
DOI: 10.1016/j.jmb.2008.03.053
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Abasic Endonuclease Activity of Human Ape1 on Alternative Substrates, as Well as Effects of ATP and Sequence Context on AP Site Incision

Abstract: Human Ape1 is a multifunctional protein with a major role in initiating repair of apurinic/ apyrimidinic (AP) sites in DNA by catalyzing hydrolytic incision of the phosphodiester backbone immediately adjacent to the damage. Besides in double-stranded DNA, Ape1 has been shown to cleave at AP sites in single-stranded (ss) regions of a number of biologically-relevant DNA conformations and in structured ssDNA. Extension of these studies has revealed a more expansive repertoire of model substrates on which Ape1 exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
114
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(130 citation statements)
references
References 50 publications
(5 reference statements)
9
114
0
1
Order By: Relevance
“…We note that this activity in RNase H is used to remove the RNA primers during DNA replication, yet there is no evidence for a role of APE1 in this process. More recent work has found that APE1 can cleave abasic sites in RNA, and it has been proposed that the protein operates in RNA quality control, removing damaged RNA templates to prevent error-prone translation, although this model has not been sufficiently validated in cells (10,215).…”
Section: Rna Cleavagementioning
confidence: 99%
See 1 more Smart Citation
“…We note that this activity in RNase H is used to remove the RNA primers during DNA replication, yet there is no evidence for a role of APE1 in this process. More recent work has found that APE1 can cleave abasic sites in RNA, and it has been proposed that the protein operates in RNA quality control, removing damaged RNA templates to prevent error-prone translation, although this model has not been sufficiently validated in cells (10,215).…”
Section: Rna Cleavagementioning
confidence: 99%
“…This research provides the strongest evidence to date of an essential role for APE1 in CSR, while implying that APE2 is not involved in this phenomenon, even as a back-up enzyme. Consistent with APE1 operating in CSR, purified recombinant APE1 protein can incise at AP sites in a synthetic oligonucleotide substrate designed to mimic the R-loop structure that is presumably needed for the recombination event (10). It is noteworthy that, to our knowledge, the contribution of APE1, or APE2 for that matter, in SHM has not been explicitly addressed.…”
Section: Participation In Specific Cellular Processesmentioning
confidence: 99%
“…Like NPM1 and NCL, APE1 is a remarkably pleiotropic protein that, in addition to possessing activity within BER, is able to independently regulate cellular redox sensing and act as a coactivator for several transcription factors (Antoniali et al 2014). Strikingly, APE1's AP-endonuclease activity has been shown to be active not only on cellular DNA but to mediate endonucleolytic cleavage of AP-containing ssRNA (Berquist et al 2008); in vivo, depletion of APE1 results in increased oxidation and AP-accumulation in ribosomal RNA and, consequently, decreased protein synthesis and cellular proliferation. These observations demonstrate that APE1 regulates a previously unappreciated 'quality control' mechanism for nucleolar rRNA (Vascotto et al 2009).…”
Section: Holding Out: Ncl Sequesters Rpa Away From the Replication Anmentioning
confidence: 99%
“…While sequestration may represent a common mechanism by which NPM1 and NCL control DNA repair dynamics, these interactions can have consequences for the activities of NPM1/NCL themselves, as demonstrated by role of p53 in the regulation of NCL nucleolar translocation (Daniely et al 2002). Additionally, the discovery of DDR-independent roles for APE1 and other NPM1-binding BER factors in nucleolar rRNA quality control (Berquist et al 2008;Guo et al 2008;Poletto et al 2014;Vascotto et al 2009) suggest that D r a f t NPM1 and/or NCL may go beyond being passive 'sponges' for such proteins and may play a key role in the coordination of their diverse cellular activities.…”
Section: Guiding Principles Of Npm1/ncl In Ddr: Chaperoning and Sequementioning
confidence: 99%
“…Therefore, all the hypotheses concerning the involvement of APE1 in the development of such pathologies should be re-interpreted in light of these findings. The role played by APE1 in RNA-related processes needs further investigations, since its ability to recognize and cleave the RNA abasic sites (12,42,89,138,149) is compatible with a leading role in the early stages of the RNA quality control process. Additional studies aiming at the understanding the mechanisms related to oxidative RNA damage processing and their consequences may provide significant insights into the pathogenesis of neurodegenerative disorders, leading to improvements in the current therapeutic strategies.…”
Section: Overview On Rna Oxidative Damages a Glimpse On Human Patholmentioning
confidence: 99%